PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PAIR CHECK TERHADAP HASIL BELAJAR FISIKA SISWA KELAS VIII SMPN 3 BATANG ANAI (Universitas PGRI Sumatera Barat, 2018)
This study is by the difficulties of students in understanding the subject matter of physics, thus resulting in low students learning outcomes. This study aims to determine the effect of the Implementation of Cooperative Learning Models Pair Check Type of Physics Learning outcomes Class VIII SMPN 3 Batang Anai. This type of research is a quasi experimental. Sampling technique with cluster random sampling. Learning outcomes in the cognitive domain obtained the average value of the experimental class students 78,13 and the control class 67,34. Then with t analysis, t count = 3,69 is greater than t- (1/2 α) = 2,01 and - t- (1/2 α) = - 2,01 (at a real level of 0.05), then the alternative hypothesis is accepted. So there is influence of applying cooperative learning models pair check type to physics learning outcomes of class VIII SMPN 3 Batang Anai Keyword: Cooperative learning, Learning outcomes, Cognitive domain.